PENGUKURAN BEBAN KERJA KARYAWAN DALAM MENGANGKAT TBS DENGAN PENDEKATAN ERGONOMI DI PT INCASI RAYA MUARA SAKAI - Tri Ernita (Sekolah Tinggi Teknologi Industri Padang, 2016)
PT Incasi Raya is one of the companies engaged in industry palm oil. The production of palm oil is mostly exported to all over the world market. The number of requests from the world market, then the company should be able to optimize the available manpower to meet demand.This study aims to determine the percentage of employees' workload of the heart's workload seen in the lifting of fresh fruit bunches using CVL method, analyze the position of the employee in the lift FFB whether in accordance with ergonomic approach. Data were analyzed quantitatively using the method of CVL (Cardiovascular load) by analyzing the positions of employees in lifting the fresh fruit bunches.Based on the results of the research, the percentage of employees receiving workload CVL biggest heart in block A with an average of 39.804% and the percentage of employees receiving CVL smallest cardiac workload on the block E with an average of 25.976% and the employee's position in the lifting of fresh fruit bunches into the dump the truck is not ergonomic. Keywords: Palm Oil, Workload, Ergonomics, Cardiovascular Load.